Analisis Distribusi Program Makan Bergizi Gratis Berdasarkan Maqasid Al-Syariah - Tiara Nur Amalina; Hana Hafidzatunnaimah; Sri Ratu Bulqiyah Tadzkir Putri; Jaenudin J; Dian Herdiana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Free Nutritious Meal Program launched by the Indonesian government in early 2025 is a strategic policy aimed at addressing malnutrition and stunting among school-aged children, pregnant women, and toddlers through the free distribution of nutritious food. This study aims to evaluate the implementation of the program using the perspective of Maqasid al-Shariah, which emphasizes the protection of life and intellect, distributive justice, and the trustworthy management of resources. The research employs a qualitative approach using in-depth interviews, field observations, and documentation studies. Data analysis is conducted descriptively by comparing implementation practices with the principles of Maqasid al-Shariah. The results show that the Free Nutritious Meal Program has a positive impact on maintaining health and supporting children’s cognitive development. However, challenges remain, including unequal distribution across regions, menu variations that are not aligned with local preferences, inconsistent portion sizes, and suboptimal supervision. The aspect of justice in target determination requires improvement to align with Islamic principles of fairness. The study recommends improving governance through a systematic monitoring system, cross-sector coordination, menu adjustments based on local wisdom, and the consistent application of halal certification. With optimal implementation of Maqasid al-Shariah principles, the program has the potential to become an effective, just, and sustainable social policy.